Two new species, one unrecorded species, and one newly reported male of genus Thiallela Walker, 1863 from China (Lepidoptera: Pyralidae: Phycitinae) - Yang, Linlin; Ren, Yingdang (Zootaxa, 2018)
The genus Thiallela Walker is a small genus with ten named species, and four of them were currently recorded from China. In the present study our new discoveries bring the total described species to twelve, with two (Thiallela celadontis sp. nov. and T. sulciflagella sp. nov.) being proposed as new, and one (T. ligeralis (Walker)) newly recorded in China. The male of T. epicrociella (Strand) is described for the first time. Photographs of the adults and the genital structures of the four species are provided. A world catalog of the genus Thiallela, a distribution map of and keys to the species known from China are also provided.